STUDY OF REOLOGICAL PROPERTIES OF CAPTOPRIL NASAL DOSAGE FORM - Аlmochаmаd Guмаа Аbdullах; V. V. Gladyishev; B. S. Burlaka; N. N. Маlеckiy (Zaporožskij Medicinskij Žurnal)
The aim of this work was to study properties of ACE inhibitor captopril semisolid dosage form which was developed on the department of technology of medication in Zaporozhye State Medical University. The complex of physico-chemical, pharmacotechnological and microbiological methods was used. As an object of study 2,5% captopril nasal dosage form on the proxanol glycerogel and the base alone were used. Study of structural-mechanical characteristics of compositions was done with the rotary viscosimeter «Reotest-2» with cylindrical arrangement.